Algorithmization and programming. Part 2: Structured data programming - Прокоп, Юлія Віталіївна; Прокоп, Ю. В.; Прокоп, Юлия Витальевна; Prokop, Yuliia V.; Трофименко, Олена Григорівна; Трофименко, О. Г.; Трофименко, Елена Григорьевна; Trofymenko, Olena H.; Буката, Людмила Миколаївна; Буката, Л. М.; Буката, Людмила Николаевна; Bukata, Liudmyla M. (Odessa, 2019)
These instructions for laboratory training and exercises contain theoretical information with examples of programs in С++ and variants of individual problems. Methodical instructions will be useful for students of the Academy of Telecommunications who are studying in English, fixing theoretical material, preparing to laboratory training and exercises in the discipline of "Algorithmization and programming" during the first semester. It is intended for the acquisition of skills in operation on a personal computer and programming by students of the academy studying in English, with the purpose of further usage of these skills in daily professional work. Also, it will be useful for users of personal computers wishing to learn programming in Visual C++ environment.
Algorithmization and programming. Part 2: Structured data programming : methodical instructions for laboratory training and exercises / Comp.: Y. V. Prokop, O. G. Trofymenko, L. N. Bukata. - Odessa, 2019. - 56 p.
Keywords: Research Subject Categories::TECHNOLOGY::Information technology